Studies of the Higgs boson using the H → ZZ → 4l decay channel with the ATLAS detector at the LHC - Garay, Francisca Montserrat; Garay Walls, Francisca (The University of Edinburgh, 2016)
Following the announcement of the discovery of a new particle on the 4th of July 2012 at the ATLAS and CMS experiments at the LHC, many efforts were needed for the understanding of its properties and to discern whether it is the Standard Model Higgs boson. The research presented in this thesis is based on the H → ZZ(*) → 4l decay channel. Three main contributions are discussed: the Standard Model Higgs boson mass measurement, the search for a heavy Higgs boson, and lastly, the implementation of a kinematic likelihood fitter as a new approach to improve the invariant mass resolution of the final states. The Standard Model Higgs boson mass measurement is presented. The measured mass is 124:51± 0:52(stat)± 0:06(syst) GeV for the combined data taken during 2011 and 2012 (4:6 fb-¹ at 7 TeV and 20:7 fb-¹ at 8 TeV). Contributing to the mass measurement, a tool was developed to validate the model used by generating several pseudo datasets from Monte Carlo samples and fitting them with the profile likelihood. The results show that the model is correct and only small deviations are seen in the parameters of interest, mH, and the signal strength, μ. Studies in the asymptotic limit show that these deviations are a symptom of low statistics in some of the final states. The search for a heavy Higgs boson is presented as well. No significant excess of events over the Standard Model prediction is found. A simultaneous fit to the profile likelihood gives 95% confidence level upper limits on the production cross-section of a heavy Higgs times the branching ratio to Z boson pairs in the mass range from 140 GeV to 1 TeV. Contributing to this search, a pseudo dataset, called Asimov dataset, is created from the Monte Carlo samples to test the profile likelihood fits and validate the model used. The results show that fit the model is correct. In addition, the limits are also interpreted in the context of Type I and Type II Two Higgs Doublet Models (2HDM). Finally, a Kinematic Likelihood Fitter (KLFitter) is studied and used to constrain the Z boson mass as an alternative to the standard tool used for the 2011 and 2012 measurement. This affects the distribution of the invariant mass, m4l, from which the Higgs boson mass is inferred. Small improvements are seen in the invariant mass resolution when higher hypothetical Higgs boson masses are considered.
Keywords: Higgs boson; Large Hadron Collider; Z bosons; Kinematic Likelihood Fitter; ATLAS; KLFitter